Pengetahuan Dan Sikap Dengan Kepemilikan Jamban Pada Masyarakat Negeri Mesa Kabupaten Maluku Tengah - Ira Sandi Tunny (Lembaga Pengembangan Kinerja Dosen, 2022)
Background. Latrine is an effective human waste disposal facility for breaking the chain of disease transmission. The role of feces in the spread of disease is very large. that is, it can directly contaminate food, drinks, vegetables, etc., as well as water, soil, insects (flies, cockroaches, etc.) and parts of our bodies can be contaminated by these feces. In the 2020 State program report, the number of residents who do not have a toilet in Mesa State is 88 heads of families (64.7%). Research purposes.To obtain information about the description of knowledge and attitudes regarding latrine ownership among the people of Negeri Mesa, Teon Nila, Serua District, Central Maluku Regency in 2021. Method.The research design used was descriptive research, the sampling technique was total sampling, with a sample size of 136 families. Research result.. From the research results, it was found that the majority of respondents had poor knowledge of open defecation behavior, namely 55 respondents (40.4%) while respondents who had good knowledge were 35 respondents (25.7%). There were 132 respondents (97.1%) who had a good attitude towards open defecation, while 4 respondents (2.9%) had a bad attitude. Conclusion.From the research results, it was concluded that in the description of the behavior of the people in this study, they still practice open defecation in Mesa Country and in the attitude category.